PHYSICAL THERAPY EXERCISE IN EARLY AND LATE POST-OPERATIVE PERIOD OF TOTAL KNEE ARTHROPLASTY: SYSTEMATIC REVIEW WITH META-ANALYSIS - Leite, Alany Gabrielli [UNESP]; Vicente, Beatriz Batista [UNESP]; de Souza Cavina, Allysiê Priscilla [UNESP]; Mantovani, Alessandra Madia; Fregonesi, Cristina Elena Prado Teles [UNESP] (Elsevier, 2024)
Background Objective: To analyze the effects of exercise-based rehabilitation on the functionality of individuals with Total Knee Arthroplasty (TKA) in the early and late postoperative period. Methods Systematic review of which studies were selected through six databases (Pubmed, PEDro, LILACS, EMBASE, CINAHL, and Cochrane Library) from January 2010 to August 2020. Only randomized clinical trials of primary unilateral TKA in the early or late postoperative period were included. All meta-analyses were conducted using Review Manager – RevMane software described as standardized mean differences with 95% confidence intervals (CI). Outcome data, including the final mean, standard deviation, and sample size values, were extracted by two reviewers. The data extraction process was performed using a standardized form and disagreements were resolved by a more experienced third author. PROSPERO Register: CRD42020200375. Results Five studies were chosen for full-text review. The main findings of this study demonstrated that physical therapy exercise, when compared to the other conditions, was effective only for the timed up and go test (three studies, n=225; MD=-1.38, 95% CI [-2.35, -0.41]; p=0.005; I²=56%). No significant differences were observed for the other analyses. Conclusion The findings of the present study demonstrate that physical therapy based on exercises, when started mainly in the early postoperative period of TKA is better than the comparison conditions in knee functionality. Implications The present review shows the clinical applicability of physiotherapeutic exercises started early after TKA, which can improve the functional conditions of patients.